OPEN GOVERNMENT, A MODEL BASED ON THREE PILLARS: TRANSPARENCY, ACCOUNTABILITY AND CITIZEN PARTICIPATION (National Administration Journal, 2019)
This paper enables to identify the most relevant conceptual aspects in relation with the open Government model. For this purpose, a bibliographic review was performed of the main lines of thought linked to this topic.  One of the most important findings of this paper is that there is no conceptual consensus yet on this subject.  However, it was possible to identify some common elements that may be used as a starting point, which has also helped adapt the model to the cultural and political characteristics of each country.  The contributions of this paper are innovative, since it is an emerging theme
Keywords: State legitimacy; governance; comparative analysis; government trends; public data